Effects of biological traits on capture-induced parturition in a freshwater stingray and perspectives for species management - Sousa Rangel, Bianca de; Castro Ribeiro, Douglas de [UNESP]; Chagas, Jumma M. A. [UNESP]; Spada, Lucas [UNESP]; Moreira, Renata G.; Silva Ribeiro, Cristiele da [UNESP] (Wiley-Blackwell, 2020)
Elasmobranchs are particularly vulnerable to overexploitation and population depletion, especially due to their life-history traits, such as low reproductive output and slow growth. Given that capture-induced parturition (abortion or premature birth) is a common consequence of fisheries in elasmobranchs, but still little studied, we investigated how the abortion/premature birth process varies in response to reproductive traits in a freshwater stingray,Potamotrygon amandae. Our results revealed that capture-induced parturition was affected by reproductive traits, such as litter size (one to seven) and gestation stage. The event occurred faster in pregnant females with high litter size during late pregnancy. Also, as found in other elasmobranchs, litter size was positively correlated with maternal size. These findings indicate that larger pregnant females in late pregnancy are more vulnerable to capture-induced parturition. This study improves our understanding of the capture-induced parturition process in stingrays, and provides useful information for management strategies and future recommendations for elasmobranch conservation.
Keywords: conservation; fisheries management; fishing stress; premature birth; upper rio Parana; viviparity